From the Spanish Periphery: Early Work by Canarian Women Architects Magüi González and Maribel Correa - Delgado Baudet, David (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Within the Spanish territory, the distant location of the Canary Islands poses an additional problem for the visibility of the work of its women architects. This article carries out analysis with a gender perspective on the professional context of women architects from the Canary Islands in the years following the Franco regime. The remoteness and island nature of the territory brought with it peculiarities which affected the way in which its professionals were trained, caused changes derived from the formation of the autonomous regions and led the professional association of architects of the Canary Islands to drive certain initiatives in a bid to promote discipline. These initiatives include the publication of the Basa journal (1982-2008) and the Manuel Oráa Architecture Prize, which marked a window of opportunity for recognition of women architects from the Canary Islands. The early careers of Magüi González and Maribel Correa, who graduated during the Transition, are useful for evaluating their thoughts on the idea of the architectural project and carrying out metacritical analysis on the way in which some of their work was received within the discourse of the prevailing narratives of the time.
Keywords: Women Architects; Manuel Oraá Prize; Basa Journal; Gender; Spanish Architecture